Pengaruh Green Trust, Green Price, dan Eco Brand Terhadap Keputusan Pembelian: (The Influence of Green Trust, Green Price, and Eco Brand on Purchase Decisions) - Vrancisco Yudha Chrysna; Hadi Sumarsono; Premi Wahyu Widyaningrum (e-Journal Ekonomi Bisnis dan Akuntansi, 2022)
The concept of green marketing has been widely accepted in both of academic and practical areas. This concept encompass all marketing activities developed to stimulate and maintain environmentally friendly attitudes and behaviors. Companies can use the concept of green marketing in formulating strategies to gain the competitive advantage. The purpose of this study is to determine the effect of Green Trust, Green Price, and Eco Brand on Purchase Decisions (Survey on Consumers of Eiger Products in Ponorogo Regency). By using accidental sampling technique, this research uses 100 customers of Eiger as respondents. The analysis used in this study using multiple linear regression analysis using the SPSS 22 program. This study proves that Green Trust, Green Price and Eco Brand have a positive and significant effect on purchasing decisions. In the case of Eiger Product in Ponorogo, the concept of green marketing is proven to be able to improve purchasing decision. The increasing of green marketing carried out by the company will further increase purchasing decisions.